1989
DOI: 10.1088/0953-4075/22/10/019
|View full text |Cite
|
Sign up to set email alerts
|

Spin asymmetries in the low-energy electron impact excitation of 2S to 2P transitions in lithium atoms

Abstract: Abstract. Crossed beams of spin-polarised lithium atoms and spin-polarised electrons with energies up to ten times the first excitation threshold have been used to measure the ratio of singlet to triplet scattering and to see the influence of exchange in excitation. The measured spin asymmetry in the intensity of the fluorescence radiation emitted perpendicular to the two beams shows substantial agreement with several close-coupling theories. Singlet scattering (A = 1) dominates near threshold but the asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These results have been analyzed to give generalized oscillator strengths and zero-angle differential cross sections for several transitions from the ground state including the 2 2 P transition. Baum et al ͓11,12͔ reported a series of experiments involving polarized electrons and polarized lithium atoms. The spin asymmetry parameter A was measured at several scattering angles for elastic scattering ͓11͔ and for the excitation of the 2 2 P state ͓12͔ for incident electron energies from 1 eV to 30 eV.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been analyzed to give generalized oscillator strengths and zero-angle differential cross sections for several transitions from the ground state including the 2 2 P transition. Baum et al ͓11,12͔ reported a series of experiments involving polarized electrons and polarized lithium atoms. The spin asymmetry parameter A was measured at several scattering angles for elastic scattering ͓11͔ and for the excitation of the 2 2 P state ͓12͔ for incident electron energies from 1 eV to 30 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 displays the spin asymmetry (A ex ) for excitation of p-states at 10 eV and 40 eV. The 10 eV experimental measurements of A ex are for 2p excitation (Baum et al 1989). Again, surprisingly, the spin asymmetry scaling is approximately valid at all scattering angles, even at rather low energies of 10 eV, but the scaling starts with N = 4 as opposed to N = 2 as was found for electron-hydrogen scattering.…”
Section: Lithiummentioning
confidence: 73%
“…The theoretical curves for different N -values are labelled in the same manner as in the upper part of figure 1. The circles are the 2p experimental results ofBaum et al (1989).…”
mentioning
confidence: 99%
“…In the past we measured A for the total electronimpact ionization of various atoms [3,5,6], the autoionization of lithium ^P states [7], and for differential elastic as well as inelastic electron scattering from lithium atoms [8,9]. The techniques for producing and monitoring polarized beams of electrons and alkali atoms have now been combined in the present experiment with the coin-cidence technique required for the study of triple-differential scattering.…”
Section: A"=|/p (4)mentioning
confidence: 99%